Newborn Screening for Sickle Cell Disease in St. Vincent and the Grenadines: Results of a Pilot Newborn Screening Program - Shelly-Ann Williams MD; Beneka Browne-Ferdinand MD; Ynolde Smart SCM, PHN; Kristen Morella MPH; Susan G. Reed DDS, DrPH; Julie Kanter MD (SAGE Publishing, 2017)
Objective: To pilot a newborn screening program for sickle cell disease (SCD) in St. Vincent and the Grenadines using a novel partnership method to determine the feasibility of a universal newborn screening program in this country. Methods : A prospective study of mothers and their newborns was conducted between January 1, 2015, and November 1, 2015, at the country's main hospital. Mothers of infants born at this hospital were offered screening for SCD for their infants. If accepted, the newborn's heel-stick blood specimen was obtained and mailed to the South Carolina Department of Health and Environmental Control Newborn Screening Laboratory for testing. Samples were analyzed for variant hemoglobins using standard laboratory techniques and results were communicated to local physicians. Feasibility was determined by a benchmark of having >50% of SCD patients receive the diagnosis and initiate disease-specific care by 3 months of age. Descriptive statistics were completed using SAS 9.4. Results : There were 1147 newborn infants screened for SCD. Of these, 123 (10.7%) had results indicative of sickle trait and 3 patients (0.3%) were diagnosed with SCD: 1 with HbSS and 2 with HbSC. All 3 patients with SCD received treatment before 3 months of age. Conclusions : A newborn screening program is feasible in this population when partnered with an established newborn screening laboratory.